(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
The development of research on educational technology over the past 50 years is examined in this study. its is accomplished by taking into account current trends and factors that have shaped its evolution. The topic is further investigated by looking at the impact these changes have had on the advancement of pedagogy for distant learning, particularly in the context of adult education. A few major current trends in educational technology research are covered in this paper. They are machine learning, learning design, social learning, personalization, and data-driven improvement. These are worth looking into since they all have roots in early research in the subject and therefore highlight some enduring issues. The study ends by recognizing the larger factors that have shaped the advancement of educational technology as well as the intricacy of the problems that the field faces and the real-world uses for it.